2021
DOI: 10.3389/fphar.2021.671589
|View full text |Cite
|
Sign up to set email alerts
|

In situ Pulmonary Artery Thrombosis: A Previously Overlooked Disease

Abstract: Pulmonary thromboembolism (PTE) is the third leading cause of death in cardiovascular diseases. PTE is believed to be caused by thrombi detached from deep veins of lower extremities. The thrombi travel with systemic circulation to the lung and block pulmonary arteries, leading to sudden disruption of hemodynamics and blood gas exchange. However, this concept has recently been challenged by accumulating evidence demonstrating that de novo thrombosis may be formed in pulmonary arteries without deep venous thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 121 publications
(161 reference statements)
3
17
1
3
Order By: Relevance
“…22 It has also been proposed that PE in the absence of DVT (or in situ pulmonary artery embolism) could be a separate entity triggered by local inflammation and ensuing imbalance in the coagulation system. 23 On the other hand, since our previous study on RA disease activity and the risk of VTE observed a somewhat stronger association between RA disease activity and PE risk, compared with DVT risk, confounding by indication cannot be ruled out as a partial explanation for our findings (but not for those from ORAL surveillance and other trials). 10 Whether, and how much, ongoing anticoagulant therapy alter the risk of VTE for patients with (or without) a history of VTE treated with any b/tsDMARD is an important clinical question; limited statistical precision precluded a detailed assessment of risks by history of VTE by anticoagulant use at treatment start and during the follow-up.…”
Section: Rheumatoid Arthritiscontrasting
confidence: 56%
“…22 It has also been proposed that PE in the absence of DVT (or in situ pulmonary artery embolism) could be a separate entity triggered by local inflammation and ensuing imbalance in the coagulation system. 23 On the other hand, since our previous study on RA disease activity and the risk of VTE observed a somewhat stronger association between RA disease activity and PE risk, compared with DVT risk, confounding by indication cannot be ruled out as a partial explanation for our findings (but not for those from ORAL surveillance and other trials). 10 Whether, and how much, ongoing anticoagulant therapy alter the risk of VTE for patients with (or without) a history of VTE treated with any b/tsDMARD is an important clinical question; limited statistical precision precluded a detailed assessment of risks by history of VTE by anticoagulant use at treatment start and during the follow-up.…”
Section: Rheumatoid Arthritiscontrasting
confidence: 56%
“…Thrombosis can also arise directly within the pulmonary vasculature. Patients at risk of in-situ pulmonary artery thrombosis display a pronounced prothrombotic phenotype, with contributions from abnormal fibrinogen variants, family history, autoimmune disease, endocrine dysregulation, and active cancer 674,686,687 . Separate to both hematological pathophysiological pathways, increased intramedullary pressure during arthroplasty procedures has been shown to embolize prothrombotic fat, bone marrow and cement fragments through systemic veins into the pulmonary vascular system 682,688,689 .…”
Section: - Does Lower Extremity Deep Venous Thrombosis Arising After ...mentioning
confidence: 99%
“…For example, PA clots contain larger quantities of fibrin, leukocytes and microparticles compared to venous thrombi [ 2 ]. This suggests that both systemic and local conditions, such as vascular endothelial cell dysfunction, hypoxia, and inflammation, likely provoke thrombosis directly in the pulmonary circulation [ 17 ]. Such systemic conditions can be mediated by circulating blood cells.…”
Section: Discussionmentioning
confidence: 99%